Development of civil and structural consultant's performance evaluation - R. Periasamy, Jayaselvi (2006)
Engineering and design activities constitute a critical link in a project’s life cycle. The consultants play a very important role for carrying out the activities. Thus an efficient project control system requires an instrument to measure and assess engineering performance among different projects. Since most of the projects in Malaysia are fast tracked, the need to evaluate the performance of consultants before a project starts is often denied. The current performances of civil and structural consultants are deteriorating especially when a lot of projects are arising and time factor is critical. Therefore, the construction works are being a failure and the integrity of the project being questioned especially when frequent unwanted incidents occur during construction and post-construction. Since 80% of the construction cost is determined by the sketch design formulated, the consultants should be very efficient and have a good performance. The aim of the study is to determine on how to evaluate the performance of consultants. The data was collected through the literature study, questionnaire survey and also interviews from clients and contractors. 50 respondents responded on the survey conducted. The questionnaire consisted of 9 factors and 33 indicators on the identification of level of performance of consultants’ service. From the analysis, 97% of the level of the performance evaluation for consultants was rated average and only 3% was rated good. Based on the analysis, a consultant performance evaluation model was established with 9 descriptions. An overall grading of the consultant’s performance was also included in the model. It was then compared with an existing model and was validated by having experts’ opinions. As a conclusion, the 3 objectives were achieved and recommendations for future study were suggested.